Development and acceptability of behavioral interventions promoting mothers' brushing of pre-school children's teeth: The preparation phase of the multi-phase optimization strategy framework - Merna Ihab; Wafaa Essam El-Din Abdelaziz; Walid Hassan; Maha El Tantawi (BMC, 2023)
Abstract Background Early childhood caries can be prevented through regular parental-supported toothbrushing, indicating the importance of behavior modification interventions targeting parents. Mobile oral health (m-oral health) interventions are gaining increased popularity although their production is not always based on solid theoretical frameworks and evidence about the efficacy of individual intervention components is not available. The Multiphase Optimization Strategy (MOST) offers a framework to develop complex m-oral health interventions and assessing the efficacy of individual components. Aim This study describes the development and assesses the acceptability of 3 intervention components using MOST to promote mothers' brushing of their preschool children's teeth. Methods The Theory of Planned Behavior guided the development of 3 components: motivational interviewing (MI), storytelling videos (STVs), and oral health promotion messages (OHPMs). A researcher received training to conduct MI. Twenty-four OHPMs were developed, and 14 STVs scripts were developed based on the "And, But, Therefore" framework. A feasibility pilot study was conducted to determine the optimization objective and assess mothers' preferences regarding the frequency and timing of receiving the intervention components. The mothers participated in a semi-structured interview to assess the acceptability of the components using 7 open-ended questions based on the framework of acceptability and thematic analysis was used to analyze the qualitative data. The mothers also responded to questions assessing the perceived and experienced acceptability of the components using close-ended questions. Descriptive statistics were presented as means and standard deviations for continuous variables and median and interquartile range for categorical variables. Results Sixteen mothers were included. The mothers expressed positive affective attitude towards the interventions. They felt the components served as "good reminders" to brush their children's teeth. However, "time" was a burden for the mothers. 80% of the mothers preferred receiving the OHPMs and STVs once per week, from 8 pm to 2 am (50%), and 60% indicated they can set 15-30 min to receiving the interventions. Conclusion The 3 components were acceptable to the mothers. The OHPMs and STVs will be sent to the mothers once per week, between 8 pm to 2 am. The MI and follow-up phone calls will be limited to 15 min.